2011
DOI: 10.1258/smj.2011.011160
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intradermal anaesthesia on success rate and pain of intravenous cannulation: a randomized non-blind crossover study

Abstract: Intravenous cannulation is a commonly performed procedure. This study aimed to determine whether the success rate and pain of intravenous cannulation is affected by prior injection of intradermal lidocaine. Intravenous cannulation was performed twice in 45 healthy volunteers. Intradermal lidocaine was administered prior to one of these cannulations. The outcome measures were success or failure of cannulation, and pain of cannulation, measured with a 100 mm visual analogue pain scale. The success rate of intrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…A recent network meta-analysis directly or indirectly compared lidocaine application with 16 further analgetic interventions before peripheral venipuncture and found that 2% lidocaine was most effective (5). However, this procedure is time-consuming (7); it can result in a higher rate of puncture failures (15,16), and of itself causes pain (8)(9)(10)16).…”
mentioning
confidence: 99%
“…A recent network meta-analysis directly or indirectly compared lidocaine application with 16 further analgetic interventions before peripheral venipuncture and found that 2% lidocaine was most effective (5). However, this procedure is time-consuming (7); it can result in a higher rate of puncture failures (15,16), and of itself causes pain (8)(9)(10)16).…”
mentioning
confidence: 99%
“…Within the trial, the 18G catheter was inserted according to the provider’s usual technique after skin cleaning without local anesthesia [which can impact insertion success 21 and its administration can also cause pain 7 ]. The provider was instructed to insert in the non-dominant arm if a suitable vein was available and to avoid veins at the antecubital fossa or upper forearm where the catheter tip will extend to the elbow crease after insertion.…”
Section: Methodsmentioning
confidence: 99%
“…cannulation is a prerequisite before any major or minor procedure. It is an invasive approach wherein a catheter is introduced into the lumen of a peripheral vein through the patient's skin (1). The pain and discomfort due to intravenous cannulation produce anxiety and stress for anyone and may lead to future negative ramifications like non-willingness for likely upcoming hospital admissions (2,3).…”
Section: Introductionmentioning
confidence: 99%